Application of Aquaculture Natural Food Produce by Protoplast Fusion Process of Dunaliella salina and Phaffia rhodozyma - Hersugondo Hersugondo; Hermin Pancasakti Kusumaningrum; Muhammad Zainuri (Marine Science Department Diponegoro University, 2010)
Recently, fishponder income tend to be static so that required an effort to accurately and efficiently one of them through aquacultures food diversification. So far, efforts to observe the pattern of introduction of a new feed, applications and their impact on aquaculture and fish farmers income has never been measured. Diversification of feed use protoplast fusion process from D. salina and P. rhodozyma which rich in natural carotenoids is needed in aquaculture because they will increase survival and body weight of animal farming. Different types of carotenoids can be combined through a process of protoplasm fusion making it cheaper, faster and efficient for diversification and development of carotenoid-rich diet. The specific objectives of this research is the development of natural food aquaculture with high carotenoid content using protoplasm fusion from the microalgae D. salina and yeast P. rhodozyma. The early stage in this research will cultivate recombinant followed by quantitative analysis of carotenoid production compared with controls. The second stage is the food diversification with different concentrations of recombinant and comparisons with commercial food followed by cost-benefit analysis. The research results have been obtained which most carotenoid-rich natural food resulted from recombinant fusion of D. salina and P. rhodozyma. Its application in vitro have increased body weight of shrimp comparing to artificial feed. In addition, recombinant food showing stable growth in both freshwater and salt water, can breed naturally and are safe for animal aquaculture consumption and also the environment. Key words : carotenoid, protoplast fusion, D. salina, P. rhodozyma, recombinant Selama ini pendapatan petani tambak cenderung statis sehingga diperlukan suatu upaya secara tepat dan efisien salah satunya melalui diversifikasi pakan. Sejauh ini usaha untuk mengamati pola introduksi suatu pakan baru, aplikasi dan dampaknya terhadap budidaya dan pendapatan petani tambak belum pernah terukur. Diversifikasi pakan mengggunakan pakan kaya karotenoid alami sangat dibutuhkan dalam budidaya perikanan karena terbukti dapat meningkatkan keloloshidupan dan menambah bobot hewan budidaya. Kedua jenis karotenoid β-karoten dan astaxantin dapat digabungkan melalui proses fusi protoplasma sehingga lebih murah, cepat dan efisien untuk diversifikasi dan pengembangan pakan kaya karotenoid. Tujuan khusus penelitian ini adalah pengembangan usaha budidaya untuk meningkatkan pendapatan petani tambak melalui diversifikasi pakan akuakultur dengan kandungan karotenoid tinggi hasil fusi protoplasma alga Dunaliella salina dan khamir Phaffia rhodozyma. Tahap awal dalam penelitian ini akan melakukan kultivasi pakan rekombinan Dunaliella salina dan Phaffia rhodozyma diikuti analisis produksi karotenoid secara kuantitatif dibandingkan dengan kontrol. Tahap kedua adalah diversifikasi pakan dengan perbedaan konsentrasi fusan dan perbandingan dengan jenis pakan lain diikuti dengan analisis untung rugi. Kata kunci : karotenoid, fusi protoplas, D. salina, P. rhodozyma, rekombinan